A Framework for Identifying the Indicators for the Impact Evaluation of the GAINEX Program - Patalinghug, Epictetus E. (Philippine Management Review; Vol 8 (1999), 2016)
This paper attempts to provide a framework in identifying the indicators for the impact evaluation of development programs.  The suggested framework is then applied to a particular development program undertaken by the Department of Science and Technology (DOST) called Gain Export Program (GAINEX).  The ultimate purpose of the framework developed in this paper is to provide a system of evaluating each project, anticipate data requirements needed for a pipeline project most likely to be approved by an implementing agency, and facilitate project monitoring vis-à-vis its stated objectives.